The Impact of the Personnel Management Information System SIMPEG on the Productivity of State Civil Servants in Sleman Regency - Ariyanto, Satria; Ilmi, Ummul; Rizki, Ridwan (Journal Social Civilecial, 2023)
This study investigates the influence of the Personnel Management Information System (SIMPEG) on the productivity of state civil servants in Sleman Regency, Indonesia. With the increasing reliance on technology in public administration, SIMPEG serves as a crucial tool for enhancing various aspects of human resource management, including recruitment, performance evaluation, and payroll management. Utilizing a quantitative methodology, data were collected from 150 civil servants through structured questionnaires, and analyzed using descriptive statistics, correlation, and regression analysis. The results reveal a significant positive correlation between SIMPEG implementation and civil servant productivity, with administrative efficiency, job satisfaction, and employee motivation identified as key contributing factors. Notably, the findings show that administrative efficiency accounts for 61% of the variance in overall work performance, underscoring the system's impact on reducing bureaucratic delays and enhancing decision-making processes. Additionally, the study highlights the importance of addressing challenges such as resistance to change and the need for adequate training to ensure successful implementation. These insights contribute to the ongoing discourse on e-government initiatives in Indonesia and provide practical recommendations for policymakers and public administrators seeking to improve service delivery and operational effectiveness. The study emphasizes the critical role of integrated personnel management systems in modernizing public administration and enhancing civil servant productivity.